Eksplorasi Campur Kode dalam Lirik Lagu “Now I Know” yang Dipopulerkan Oleh Kaleb J - Balqies Aulia Zhia Ulhaq (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research discusses the use of code-mixing in the lyrics of the song “Now I Know” by Kaleb J. Code-mixing, in the form of the insertion of English elements into Indonesian lyrics, often appears in modern music as a response to globalization. A qualitative research approach is used to identify the forms of code-mixing (words, phrases, and clauses), its function, and its impact on the song's message. The results of the analysis show that code-mixing dominates the chorus with English to accentuate emotional intensity, while Indonesian is present in the verses to provide a narrative that is familiar to local listeners. The use of two languages reflects a balance between local and global elements, enhancing the musical aesthetics and international appeal of the song. Intercoding acts as a linguistic and artistic tool that expands the range of listeners, supports the themes of love and regret, and strengthens pop music's connection to globalization trends.